Faint submillimeter galaxies identified through their optical/near-infrared colors: 1. Spatial clustering and halo masses - Chen (陳建州), Chian-Chou; Smail, Ian; Swinbank, A.M.; Simpson, James M.; Almaini, Omar; Conselice, Christopher J.; Hartley, Will G.; Mortlock, Alice; Simpson, Chris; Wilkinson, Aaron (American Astronomical Society, 2016)
The properties of submillimeter galaxies (SMGs) that are fainter than the confusion limit of blank-field single-dish surveys (S850  2 mJy) are poorly constrained. Using a newly developed color selection technique, Optical-Infrared Triple Color (OIRTC), that has been shown to successfully select such faint SMGs, we identify a sample of 2938 OIRTC-selected galaxies, dubbed Triple Color Galaxies (TCGs), in the UKIDSS-UDS field. We show that these galaxies have a median 850 μm flux of S850 = 0.96 +/- 0.04 mJy (equivalent to a star formation rate SFR ~60–100 M yr−1 based on spectral energy distribution fitting), representing the first large sample of faint SMGs that bridges the gap between bright SMGs and normal star-forming galaxies in S850 and LIR. We assess the basic properties of TCGs and their relationship with other galaxy populations at z ~ 2. We measure the two-point autocorrelation function for this population and derive a typical halo mass of log10(Mhalo) = -12.9+0.2-0.3, 12.7+0.1,-0.2, and 12.9+0.2,-0,3 h-1 M at z = 1–2, 2–3, and 3–5, respectively. Together with the bright SMGs (S850 >/~ 2 mJy) and a comparison sample of less far-infrared luminous star-forming galaxies, we find a lack of dependence between spatial clustering and S850 (or SFR), suggesting that the difference between these populations may lie in their local galactic environment. Lastly, on the scale of ~8–17 kpc at 1 < z < 5 we find a tentative enhancement of the clustering of TCGs over the comparison star-forming galaxies, suggesting that some faint SMGs are physically associated pairs, perhaps reflecting a merging origin in their triggering.